Effect of liraglutide on dietary lipid‐induced insulin resistance in humans. Issue 1 (10th August 2017) - Koska, Juraj; Lopez, Lizette; D'Souza, Karen; Osredkar, Tracy; Deer, James; Kurtz, Julie; Salbe, Arline D.; Harman, Sherman M.; Reaven, Peter D.
Abstract : Aims: To test whether liraglutide suppresses postprandial elevations in lipids and thus protects against high saturated fatty acid (SFA) diet‐induced insulin resistance. Methods: In a randomized placebo‐controlled crossover study, 32 participants with normal or mildly impaired glucose tolerance received liraglutide and placebo for 3 weeks each. Insulin suppression tests (IST) were conducted at baseline and after a 24‐hour SFA‐enriched diet after each treatment. Plasma glucose, insulin, triglycerides and non‐esterified fatty acids (NEFA) were measured over the initial 8 hours (breakfast and lunch) on the SFA diet. A subset of participants underwent ex vivo measurements of insulin‐mediated vasodilation of adipose tissue arterioles and glucose metabolism regulatory proteins in skeletal muscle. Results: Liraglutide reduced plasma glucose, triglycerides and NEFA concentrations during the SFA diet (by 50%, 25% and 9%, respectively), and the SFA diet increased plasma glucose during the IST (by 36%; all P  < .01 vs placebo). The SFA diet‐induced impairment of vasodilation on placebo (−9.4% vs baseline; P  < .01) was ameliorated by liraglutide (−4.8%; P  = .1 vs baseline). In skeletal muscle, liraglutide abolished the SFA‐induced increase in thioredoxin‐interacting protein (TxNIP) expression (75% decrease; P  < .01 vs placebo) and increased 5′AMP‐activated protein kinase (AMPK) phosphorylation (50% vs −3%; P  = .04 vs placebo). Conclusions: Liraglutide blunted the SFA‐enriched diet‐induced peripheral insulin resistance. This effect may be related to improved microvascular function and modulation of TxNIP and AMPK pathways in skeletal muscle.